Apoptotic mechanisms in rabbits with blast-induced acute lung injury - Qi,Xiao-Lin (2018)
Abstract Purpose: To investigate the apoptotic mechanisms in rabbits with blast-induced acute lung injury (ALI). Methods: A total of 40 rabbits were randomly divided into a blank control group (A, n=10) and an experimental group (EXP, n=30). Explosion-induced chest-ALI models were prepared and sampled at different time points (4, 12, and 24h after modeling, T1-T3) to test the lung dry weight/wet weight ratio (W/D) and arterial oxygen pressure (PaO2), apoptosis of lung tissue by the TUNEL assay, and Caspase-3, Bax, and Bcl-2 levels by immunohistochemical analysis. Furthermore, lung tissue was sampled to observe pathological morphology by microscopy. Results: Under a light microscope, Group EXP exhibited obvious edema in the pulmonary interstitial substance and alveoli, a large number of red blood cells, inflammatory cells, and serous exudation in the alveolar cavity, as well as thickening of the pulmonary interstitial fluid. Compared to Group A, the W/D ratio was significantly increased in Group EXP (P<0.01), while PaO2 was significantly reduced (P<0.01). The apoptosis index was significantly increased (P<0.01), and caspase-3 and Bax/Bcl-2 levels were increased (P<0.01). Conclusion: Apoptosis plays an important role in the occurrence and development of acute lung injury in rabbits by participating in lung injury and promoting the progression of ALI.